Review of sport injures for teams and athletes - Zenkova, T. A.; Shengelaya, S. A.; Groshevikhin, I. V.; Chabovskiy S. Y. (Theory and Practice of Physical Culture, 2024)
Objective of the research was to analyses the causes and conduct a comparative analysis of the causes and consequences and the incidence of injuries for sport teams and athletes.